Strategies for Internalizing Hadith about Compassion in Reducing Bullying Behavior in SDII Tamaddunia Mulia - Alma'arif, Alma'arif; Muslim, Muslim (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study examines the internalization of the hadith on rahmah (affection) as a strategy for reducing bullying behavior in an Islamic elementary school. Using a qualitative case study approach, the research was conducted at SDII Tamaddunia Mulia, where the memorization and internalization of Sunan Abi Dawud Hadith number 4941 are integrated into character education. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings indicate that hadith memorization functions not merely as a cognitive activity but as a transformative process that converts religious knowledge into lived moral practice. The internalization of compassion is strengthened through teacher role-modeling, reflective habituation, and parental involvement, leading to increased empathy, spontaneous prosocial behavior, and a notable decline in bullying incidents. The study further reveals that religious knowledge is constructed through the integration of scriptural teachings, social interaction, and personal experience, resulting in the development of tacit moral awareness among students. This research contributes to the epistemology of Islamic education by demonstrating how hadith can function as operational knowledge that shapes social behavior. It recommends complementing memorization-based character education with reflective and participatory learning strategies, while strengthening collaboration among schools, families, and communities to sustain anti-bullying initiatives grounded in religious values.